2000
DOI: 10.2105/ajph.90.10.1629
|View full text |Cite
|
Sign up to set email alerts
|

Hunger in legal immigrants in California, Texas, and Illinois

Abstract: A B S T R A C TObjectives. This study determined the prevalence of food insecurity and hunger in low-income legal immigrants.Methods. We conducted a cross-sectional survey of Latino andAsian legal immigrants attending urban clinics and community centers in California, Texas, and Illinois with a food security questionnaire.Results. Among 630 respondents, 40% of the households were food insecure without hunger and 41% were food insecure with hunger. Independent predictors of hunger were income below federal pove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 7 publications
1
22
2
Order By: Relevance
“…1, 57 A 2000 study of low-income Latino and Asian immigrants in urban areas in California, Texas, and Illinois found that 81% of households were food insecure and that Latino ethnicity and poor English were positive predictors of hunger. 6 Latino immigrants surveyed at an urban medical center in Minneapolis had significantly higher rates of household food insecurity compared to U.S.-born non-Latinos. 8 In a study of mothers across seven U.S. cities, households with immigrant mothers were at greater risk of food insecurity than those with U.S. born mothers, and food insecurity increased the risk of poor child health.…”
mentioning
confidence: 90%
“…1, 57 A 2000 study of low-income Latino and Asian immigrants in urban areas in California, Texas, and Illinois found that 81% of households were food insecure and that Latino ethnicity and poor English were positive predictors of hunger. 6 Latino immigrants surveyed at an urban medical center in Minneapolis had significantly higher rates of household food insecurity compared to U.S.-born non-Latinos. 8 In a study of mothers across seven U.S. cities, households with immigrant mothers were at greater risk of food insecurity than those with U.S. born mothers, and food insecurity increased the risk of poor child health.…”
mentioning
confidence: 90%
“…Being younger, having minority status (particularly African-American or Hispanic), being a single mother, and having low levels of education increase the risk of food insecurity (Bartfeld and Dunifon 2006; Connell et al 2001; Daponte and Stephens 2004; Dunifon and Kowaleski-Jones 2003; Kasper et al 2000; Nord et al 2004; Olson et al 1997; Opsomer et al 2003; Ribar and Hamrick 2003a; Rose et al 1998). Poor mental health, disability, and chronic physical health conditions not only increase the likelihood of being food-insecure but are also associated with more severe levels of food insecurity among households experiencing food hardship (Coleman-Jensen and Nord 2013; Tarasuk et al 2013).…”
Section: Food Insecurity and Previous Researchmentioning
confidence: 99%
“…Household food insecurity, defined as, “limited or uncertain availability of nutritionally adequate and safe foods or limited or uncertain ability to acquire foods in a socially acceptable way (1),” is more likely to affect low-income, minority groups in the United States (US) (28). According to the 2007 Current Population Survey of US Households, 11.1% of all households in the US were classified as food insecure whereas 20.1% of Hispanics reported food insecurity (9).…”
Section: Introductionmentioning
confidence: 99%